Strategies of Persuasive Discourse in the Sermons of the Great Mosque of Mecca: An Analytical Study - Rababa, محمد أحمد حسن; Alnady, أحمد محمد أحمد (Dirasat: Shari'a and Law Sciences, 2022)
Objectives: The study aimed to track persuasive discourse strategies in the sermons of the Great Mosque of Mecca and the extent to which the preachers of it took into account the use of these strategies in their pulpit sermons in the Great Mosque of Mecca. Methods: The study adopted the descriptive approach in the manner of content analysis of a sample of the sermons of the Great Mosque of Mecca, and analyzed 53 sermons delivered in the Great Mosque of Mecca during the Hijri year 1442 AH. The analysis relied on a special tool (content analysis form) built by the researchers and was judged by a jury of specialists. Results: The results showed that the strategy of using reliable citations from the Holy Qur’an and the correct and good Sunnah came in the first place, and measurement and reflection came in the first and second place among other mental methods. The results also showed a great interest from the preachers in the strategy of recalling stories of various kinds. In addition, most of the preachers of the Haram are keen to employ the structural and constructivist skills in their sermons, including the precise rhythm, rhyme, and the absence of melody. Conclusions: The necessity of training and qualifying preachers and preachers on the mechanism of employing persuasive discourse strategies, and the need for preachers to take care these strategies in their speeches, sermons and advocacy messages